Epigenetics as a basis for diagnosis of neurodevelopmental disorders: challenges and opportunities. (July 2014) - Kubota, Takeo; Miyake, Kunio; Hariya, Natsuyo; Mochizuki, Kazuki
<x xml:space="preserve">Abstract</x> Neurodevelopmental disorders, such as autism, are complex entities that can be caused by biological and social factors. In a subset of patients with congenital neurodevelopmental disorders, clear diagnosis can be achieved using DNA sequence-based analysis to identify changes in the DNA sequence (genetic variation). However, it has recently become clear that changes to the secondary modifications of DNA and histone structures (epigenetic variation) can also cause neurodevelopmental disorders via alteration of neural gene function. Moreover, it has recently been demonstrated that epigenetic modifications are more susceptible to alterations induced by environmental factors than are DNA sequences, and that some drugs commonly used reverse mental-stress induced alterations to histone modifications in neural genes. Therefore, application of diagnostic assays to detect epigenetic alterations will provide new insight into the characterization and treatment of neurodevelopmental disorders.